THE EFFECT OF INFOGRAPHIC MEDIA IN DISCOVERY MODEL ON STUDENTS’ MOTIVATION AND LEARNING OUTCOMES - Zahrah, St.; Ramlawati, Ramlawati; Muhiddin, Nurhayani H. (Universitas Negeri Makassar, 2024)
This study aims to determine (1) The level of motivation and learning outcomes using infographics and conventional media (2) The increase in motivation and learning outcomes after using infographics and conventional media (3) The effect of using infographics on motivation and learning outcomes. This type of research is a Quasi-Experiment with Nonequivalent Control Group Design. The sample was selected by purposive sampling. The research instrument is a motivation questionnaire and learning outcomes test. Research results: (1) The level of learning motivation before and after the use of infographics in the medium category with a score of 64.45 and a high category with a score of 83.31. The level of learning outcomes before and after the use of infographics in the low category with a score of 8.38 and the high category with a score of 16.86 (2) The increase in motivation and learning outcomes after the use of infographics in the medium category with a score of 0.53 and 0.51, after the use of conventional media in the medium category with a score of 0.33 and 0.39 (3) There is an effect of using infographic media on motivation and learning outcomes of class VIII students of SMPN 2 Sungguminasa.